PENINGKATAN LEBAR PITA TRANSMISI DENGAN MEMANFAATKAN SIFAT NON LINIER SERAT OPTIK - Waluyo
Dispersion of the transmitted optical signal causes distortion along optical fibers. In this way the dispersive properties determine the limit of information capacity of the fiber. To overcome this problem, we propose to exploit the nonlinear dependence of the index of refraction on intensity. This can cause an effect called self-phase modulation. It makes the leading edge of the pulse to develop a red-shift and the trailing edge to develop a blue shift. The effects of fiber dispersion (in the case anomalous dispersion) are exactly compensated by the fiber nonlinearity (self phase modulation) when the input has a hyperbolic secant shape.The optical pulse can propagate in optical fibers without any dispersive change which is called a soliton (solitary wave). Such a pulse provides big advantage for a high bitrate optical transmission system. Computer simulation tests were carried out using split-step fourier method to show the performance of the proposed solution.